Sequential one-pot three-step synthesis of polysubstituted 4-(5-(trifluoromethyl)-1H-pyrazol-4-yl)-1H-1, 2, 3-triazole systems. Issue 69 (11th September 2017) - Bonacorso, Helio G.; Dal Forno, Gean M.; Wiethan, Carson; Ketzer, Alex; Zanatta, Nilo; Frizzo, Clarissa P.; Martins, Marcos A. P.; Stradiotto, Mark
Abstract : Sequential one-pot, three-step synthesis of polysubstituted 4-(5-(trifluoromethyl)-1 H -pyrazol-4-yl)-1 H -1, 2, 3-triazoles. Abstract : This work reports a successful one-pot three-step protocol for the synthesis of a new series of 15 examples of polysubstituted 4-(5-(trifluoromethyl)-1 H -pyrazol-4-yl)-1 H -1, 2, 3-triazoles, in which sequential Sonogashira cross-coupling, desilylation, and a copper(i )-catalyzed azide–alkyne cycloaddition reaction (CuAAC) with an overall yield of up to 72% were used. The presence of a trifluoromethyl substituent attached to the pyrazole moiety made the Sonogashira cross-coupling reaction challenging. Additionally, the selection of the ancillary ligand XPhos was essential and indispensable for the desired heterocyclic construction.